Pollyanna - Porter, Eleanor H. (Dover Publications, 2008)
When Pollyanna's farther dies, she goes to live with her Aunt, Miss Polly Harrington. Miss Harrington likes doing good, but she doesn't like children very much! Pollyanna always tries to find the good in everything. She soon makes many different people in her new home feel happier. But is Miss Polly's life going to change for better or worse after her niece arrives? And what happens to Pollyanna when she has a very bad accident?